Variations in urban traffic volumes - Thomas, Tom; Weijermars, Wendy; Berkum, Eric van (European Journal of Transport and Infrastructure Research, 2008)
This paper describes the variation in traffic volumes in the Dutch city of Almelo. For this study, we used traffic counts which were collected at about 20 intersections from September 2004 until September 2005. The objective of this study is to provide insight in both periodic and random variation in urban traffic volumes. This insight is used by policy makers and traffic managers to determine a suitable set of traffic measures. It is also a basis for short term predictions of volumes. We conclude that we can distinguish the following types of variation with respect to the average daily volume profile. (1) Seasonal variations with time-scales of weeks and weekly variations that describe the variation from day to day. These variations can be as large as 10% for the city of Almelo. (2) Periodic variations at time-scales of typically 30 minutes. These variations are recurrent and are often larger than 10%. (3) Noise. This variation has a random character. We show that the noise can be approximated by a Poisson distribution.